Prognostic significance of Tet methylcytosine dioxygenase 2 (TET2) gene mutations in adult patients with acute myeloid leukemia: a meta-analysis. Issue 12 (December 2014) - Liu, Wen-Jian; Tan, Xiao-Hong; Luo, Xiu-Ping; Guo, Bao-Ping; Wei, Zhou-Ji; Ke, Qing; He, Sha; Cen, Hong
Abstract Tet methylcytosine dioxygenase 2 (TET2) gene mutations have recently been recognized in acute myeloid leukemia (AML). We performed a meta-analysis to evaluate the controversial prognostic significance of TET2 mutations in AML. Eight studies, covering 2552 patients with AML, were included in this analysis. Pooled hazard ratios (HRs) indicated that TET2 mutations had a poor prognostic impact on the survival of patients with AML. The combined HR for overall survival (OS) was 1.53 and the summary HR for event-free survival (EFS) was 1.64. Additionally, TET2 mutations appeared to be an adverse prognostic indicator in both patients with cytogenetically normal (CN)-AML (HR for OS: 1.43 and HR for EFS: 1.76) and subgroups of patients with favorable-risk genotypes (HR for EFS: 2.35) and intermediate-I-risk genotypes (HR for EFS: 1.57). These findings indicate that TET2 mutations have an adverse impact on prognosis and may help to justify risk-adapted therapeutic strategies for patients with AML.